Strengthening Indonesia's defense capability through AI-driven decision-making - Djansena, Alradix; Supriyadi, Asep Adang; Kartiningsih, Yuli; Yusman, Faisal; Saleh, Basuki Rahmad (Jurnal Praksis dan Dedikasi Sosial, 2025)
The emergence of Artificial Intelligence (AI) in the Fourth Industrial Revolution has redefined the dynamics of modern military systems, especially in areas such as strategic decision-making, threat anticipation, and cybersecurity. While global powers like the United States, China, and the European Union have institutionalized AI within their defense doctrines, Indonesia is still in the developmental phase. This is particularly concerning given the intensifying security landscape and digital threats requiring an agile and intelligent defense framework. This study applies a qualitative methodology by integrating document-based analysis with cross-country comparative evaluation. It investigates how AI has been embedded into the defense architectures of leading countries and assesses the relevance and adaptability of these strategies for Indonesia’s national security needs. AI technologies benefit defense systems, such as real-time decision support, automated logistics, and enhanced situational awareness through machine learning algorithms. Nonetheless, several challenges remain, including ethical issues, algorithmic bias, cyber vulnerabilities, Indonesia’s limited digital infrastructure, and AI-specialized human capital. The U.S. emphasizes explainable AI (XAI) and operational integrity, China focuses on rapid militarization of AI, while the EU promotes regulation, ethics, and collaborative defense. Indonesia must accelerate the transformation of its defense policies by cultivating a national AI ecosystem, reinforcing its cybersecurity architecture, ensuring transparent and ethical governance, and prioritizing capacity building for AI professionals. A synergistic collaboration among the government, academic institutions, and defense industries is crucial to align AI deployment with Indonesia’s national security goals. This research introduces a conceptual framework for AI policy reform tailored to Indonesia's geopolitical and technological context, offering an integrated model for ethical, scalable, and strategic AI implementation in the defense sector.